Spatial and functional structure of an entire ant assemblage in a lowland Panamanian rainforest - Leponce, Maurice; Corbara, Bruno; Delabie, Jacques H.C.; Orivel, Jérôme; Aberlenc, Henri Pierre; Bail, Johannes; Barrios, Hector; Campos, Ricardo I.; do Nascimento, Ivan Cardoso; Compin, Arthur; Didham, Raphaël K.; Floren, Andreas; et al. (Basic and Applied Ecology, 2021)
Ants are a major ecological group in tropical rainforests. Few studies in the Neotropics have documented the distribution of ants from the ground to the canopy, and none have included the understorey. A previous analysis of an intensive arthropod study in Panama, involving 11 sampling methods, showed that the factors influencing ant β diversity (i.e., changes in assemblage composition) were, in decreasing order of importance, the vertical (height), temporal (season), and horizontal (geographic distance) dimensions. In the present study, we went one step further and aimed (1) to identify the best sampling methods to study the entire ant assemblage across the three strata, (2) to test if all strata show a similar horizontal β diversity and (3) to analyze the functional structure of the entire ant assemblage. We identified 405 ant species from 11 subfamilies and 68 genera. Slightly more species were sampled in the canopy than on the ground; they belonged to distinct sub-assemblages. The understorey fauna was mainly a mixture of species found in the other two strata. The horizontal β diversity between sites was similar for the three strata. About half of the ant species foraged in two (29%) or three (25%) strata. A single method, aerial flight interception traps placed alongside tree trunks, acting as arboreal pitfall traps, collected half of the species and reflected the vertical stratification. Using the functional traits approach, we observed that generalist species with mid-sized colonies were by far the most numerous (31%), followed by ground- or litter-dwelling species, either specialists (20%), or generalists (16%), and arboreal species, either generalists (19%) or territorially dominant (8%), and finally army ants (5%). Our results reinforce the idea that a proper understanding of the functioning of ant assemblages requires the inclusion of arboreal ants in survey programs.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Ant diversity; Ant sampling methods; Canopy; Colony size; Feeding habits; Functional groups; Horizontal β diversity; Nesting mode; Vertical stratification